2019
DOI: 10.1002/ps.5532
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and limitations of Bacillus thuringiensis galleriae for managing Japanese beetle (Popillia japonica) adults and grubs with caveats for cross‐order activity to monarch butterfly (Danaus plexippus) larvae

Abstract: BACKGROUND: Target-selective biopesticides are needed to facilitate integrated pest and pollinator management in urban landscapes and gardens. Bacillus thuringiensis galleriae, strain SDS-502 (Btg), recently registered in the USA and Canada, produces Cry8Da protein active against scarab beetles. We evaluated Btg formulations for managing the Japanese beetle [Popillia japonica Newman (JB)], a polyphagous invasive pest, including residual spray effectiveness for reducing adult feeding on Rosa and Tilia spp., and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Larval mortality ranged between 50–80% and 27–60%, respectively, for L. oryzophilus and H. postica 20,25 . For adults, a 50–90% reduction in defoliation and 50–80% mortality were recently reported for the Japanese beetle ( Popillia japonica , Coleoptera: Scarabaeidae) 26 and 100% mortality for the bean weevil Acanthoscelides obtectus (Coleoptera: Chrysomelidae) 37 . In contrast, adult mortality of the Emerald ash borer ( Agrilus planipennis , Coleoptera: Buprestidae) was reported to be somewhat lower and varied between 20% and 50%, with 4 days until first death after exposure to Bt galleriae SDS‐502 23 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Larval mortality ranged between 50–80% and 27–60%, respectively, for L. oryzophilus and H. postica 20,25 . For adults, a 50–90% reduction in defoliation and 50–80% mortality were recently reported for the Japanese beetle ( Popillia japonica , Coleoptera: Scarabaeidae) 26 and 100% mortality for the bean weevil Acanthoscelides obtectus (Coleoptera: Chrysomelidae) 37 . In contrast, adult mortality of the Emerald ash borer ( Agrilus planipennis , Coleoptera: Buprestidae) was reported to be somewhat lower and varied between 20% and 50%, with 4 days until first death after exposure to Bt galleriae SDS‐502 23 .…”
Section: Discussionmentioning
confidence: 96%
“…In this pilot study, we tested concentrations suggested by product labels and previous literature examining the effect of these formulations (not transgenic plants) on Coleopteran late-instar larvae or adults (if available), and in Diptera for Bt. [22][23][24][25][26] Concentrations (percentage of product in treatment solution; mass or liquid to volume ratios, g:vol or vol:vol) ranged from 0.1% to 25% in these studies and instructions, depending on the strain. As in previous studies, we took into account the number of colony-forming units (CFU; no.…”
Section: Testing Toxicity Of Individual Bt Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Bt strains are assumed to be selective on target pests, recent reports indicate cross-order effects (van Frankenhuyzen et al 2017). For example, the Coleopteran-targeted formulation can cause negative effects on Lepidopteran (Redmond et al 2020), the Lepidopteran-targeted formulation on Coleopteran and the Dipteran (Coyle et al 2000;Babin et al 2020;Nawrot-Esposito et al 2020), and Diptera-targeted formulation on Coleopteran (Tudoran et al 2020). Regarding the effects on bees, differences in the sensitivity of adult worker bees to different Bt products were reported (Brighenti et al 2007;Mommaerts et al 2010;D'urso V, Mazzeo G, Vaccalluzzo V, Sabella G, Bucchieri F, Viscuso R, Vitale DG, , 2017;Libardoni et al 2018;Potrich et al 2018;Steinigeweg et al 2021).…”
Section: Bt Concentrations In Dead Beesmentioning
confidence: 99%
“…The most studied insecticidal toxins are Cry-toxins as δ-endotoxins affecting the susceptible insects after oral uptake (Bravo et al 2011 andBravo et al, 2017;Mendoza-Almanza et al 2020). Several reports regarding direct and indirect cross-effects of Bt formulations and their toxins across insect taxa and orders recently indicated the semi-specificity of Bt (van Frankenhuyzen 2017; Redmond et al 2020;Coyle et al 2000;Babin et al 2020;Nawrot-Esposito et al 2020;Tudoran et al 2020). Lepidopterantargeted formulation, containing Bta ABTS 1857, has demonstrated increasing mortality of adult and larvae of honeybees after chronic exposure under laboratory conditions (Steinigeweg et al 2021).…”
Section: Introductionmentioning
confidence: 99%